Development of Reference Retrieval System with Simultaneous Building up of Thesaurus for Industrial Information Centres (Thesaurus Series. 5) - Sudarshan, B. (Journal of Information and Knowledge, 1979)
In the development of a reference retrieval system, one of the common problems faced is that whether to build a thesaurus first and then use it for indexing the documents or to index the documents by free terms and then construct the thesaurus after accumulating a good number of terms. In most of the cases a via-media between the two is advantageous. This article discusses the above problem and suggests a method of developing a reference retrieval system in which building up of the index file and thesaurus go hand in hand.